2022
DOI: 10.3389/fimmu.2022.841835
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Microbiota Vaccine Reduces Avian Malaria Infection Within Mosquito Vectors

Abstract: Animal and human pathogens that are transmitted by arthropods are a global concern, particularly those vectored by mosquitoes (e.g., Plasmodium spp. and dengue virus). Vector microbiota may hold the key to vector-borne pathogen control, as mounting evidence suggests that the contributions of the vector microbiota to vector physiology and pathogen life cycle are so relevant that vectorial capacity cannot be understood without considering microbial communities within the vectors. Anti-tick microbiota vaccines ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Reducing network robustness by anti‐microbiota vaccines presents a novel strategy to impact vector microbiota, as demonstrated by Mateos‐Hernández et al (2021). This approach aims to induce infection‐refractory states in ticks or other vectors, as highlighted by Maitre, Wu‐Chuang, Aželytė, et al (2022) and Maitre, Wu‐Chuang, Mateos‐Hernández, et al (2022), ultimately leading to a reduction or blockade of vector‐borne pathogen transmission (Aželytė et al, 2022). Previous research showed that anti‐microbiota vaccines that targets keystone taxa can modulate the tick microbiota (Mateos‐Hernández et al, 2020, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing network robustness by anti‐microbiota vaccines presents a novel strategy to impact vector microbiota, as demonstrated by Mateos‐Hernández et al (2021). This approach aims to induce infection‐refractory states in ticks or other vectors, as highlighted by Maitre, Wu‐Chuang, Aželytė, et al (2022) and Maitre, Wu‐Chuang, Mateos‐Hernández, et al (2022), ultimately leading to a reduction or blockade of vector‐borne pathogen transmission (Aželytė et al, 2022). Previous research showed that anti‐microbiota vaccines that targets keystone taxa can modulate the tick microbiota (Mateos‐Hernández et al, 2020, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial assembly within arthropod vectors influence pathogen ecology and transmission ( Aželytė et al, 2022 ). The detection of bacterial taxa in the same physical space (i.e., tick tissues) could be an indication of direct interactions between microbes ( Gomard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One promising approach is to vaccinate vertebrate hosts against mosquito gut bacteria, generating antibodies that target specific bacteria and suppress their growth in mosquitoes, thereby inhibiting pathogen infection. For instance, experimental infection of domestic canaries with Plasmodium relictum , followed by immunization with Enterobacteriaceae, results in the production of bacteria-specific antibodies ( Aželytė et al, 2022 ). Culex quinquefasciatus fed on the infected and immunized birds or birds only immunized have an altered abundance of multiple bacterial taxa in the mosquitoes’ midguts compared to mosquitoes fed on unimmunized counterparts.…”
Section: The Mosquito Microbiomementioning
confidence: 99%